Pengaruh Kualitas Pelayanan Harga dan Lokasi Terhadap Kepuasan Pelanggan Pada Penginapan Wisma Jampea Makassar - Ma’bud, Muhammad A. Rubi; Mas’ud, Masdar; Nurpadila, Nurpadila (Innovative: Journal Of Social Science Research, 2024)
Abstract The Impact of Service Quality, Price and Location on Customer Satisfaction at Wisma Jampea Makassar Lodging This research rigorously aimed to investigate the current customer satisfaction at Wisma Jampea customers. The variables used consisted of service quality (X1), price (X2), location (X3), and Customer Satisfaction (Y). Further, this study included 53 respondents as samples and conducted quantitative research using primary data. Thus, this research collected the data from questionnaires. The population of this study involved 53 Visitors then performed survey method as sampling techniques. Afterwards, this research applied analytical methods including validity tests, data reliability tests, normality tests, multicollinearity tests, heteroskedasticity tests, multiple linear regression analysis, simultaneous influence tests (F tests), partial influence tests (t) and R2 simultaneous determination tests. Therefore, the results showed that: (1) Service Quality indicated a positive influence on Customer Satisfaction at Wisma Jampea Makassar Lodging; (2) price reported a non-positive effect on Customer Satisfaction at Wisma Jampea Makassar Lodging; (3) location found a positive impact on Customer Satisfaction at Wisma Jampea Makassar Lodging. Keywords: Service Quality, Price, Location and Customer Satisfaction